Total phenolic content and free radical scavenging activity of extracts from selected plants of ukrainian flora: potential for application in functional food technologies - Ivanova, Victoria; Arsenieva, Larisa (My University, 2012)
Last years the search for new sources of natural antioxidants, especially of plant origin, has been increased. Their presence in functional foods may provide a physiological effect on the human organism, helps to reduce the risk of certain diseases (eg inflammatory, cardiovascular, tumor). Phenolic compounds are an important class of secondary plant metabolites and potent free radical scavengers because they can donate their alcoholic hydrogen atom to free radicals. В останні роки посилився пошук нових джерел природних антиоксидантів, особливо рослинного походження. Їх присутність у функціональних харчових продуктів може забезпечити фізіологічну дію на організм людини, допомагає знизити ризик деяких захворювань (наприклад, протизапальних, серцево-судинних, пухлинних).
Keywords: extract; экстракт; екстракт; кафедра експертизи харчових продуктів